2020
DOI: 10.1111/cxo.13054
|View full text |Cite
|
Sign up to set email alerts
|

A holistic model of low vision care for improving vision‐related quality of life

Abstract: Vision impairment can have a significant impact on the wellbeing and quality of life of an individual. Vision rehabilitation has the potential to improve these areas; however, four in five patients with vision impairment are not being referred to the appropriate services. Barriers to on-referral include, but are not limited to: (1) misunderstandings by both practitioners and patients alike regarding which individuals with vision impairment might benefit or qualify for low vision services; (2) lack of awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Although multiple practice guidelines have emphasized the importance of referral to LVR [ 13 ], only 5–10% of patients who qualify for LVR services end up obtaining them [ 17 ]. In a review study, Luu et al [ 18 ] identified potential barriers to accessing LVR services and proposed a holistic model of low-vision care for improving vision-related quality of life. Barriers identified in this study included lack of appropriate referrals by optometrists and ophthalmologists due to unawareness of available services and lack of patient understanding about the referrals.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple practice guidelines have emphasized the importance of referral to LVR [ 13 ], only 5–10% of patients who qualify for LVR services end up obtaining them [ 17 ]. In a review study, Luu et al [ 18 ] identified potential barriers to accessing LVR services and proposed a holistic model of low-vision care for improving vision-related quality of life. Barriers identified in this study included lack of appropriate referrals by optometrists and ophthalmologists due to unawareness of available services and lack of patient understanding about the referrals.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of shared decision making, and patients' involvement are widely reported in the literature, 43,44 suggesting that patient participation often results in improved rehabilitation of patients. 45 Patient-centred care leads to increased uptake of service, greater health literacy, improved self-care, increased satisfaction with services and improved patient-clinician relationships. 43 In addition, the importance of involving patients in decisions about their care is highlighted in professional guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical framework of the intervention design was based on Luu et al .’s Quality of Life (QoL) model 45 . This model has four dimensions: (i) physical factors, (ii) functional factors, (iii) social factors and (iv) psychological factors.…”
Section: Methodsmentioning
confidence: 99%